Antagonismo de Trichoderma virens en el control de Rhizoctonia solani en Phaseolus vulgaris var. Caupì - Alfaro Gil, Leyddy Belu (2019)
The objective of this study was to determine the antagonism of Trichoderma virens in the control of Rhizoctoni solani in Phaseolus vulgaris var.cowpea. Two strains of T. virens and one strain of R. solani were used, which were evaluated individually and then compared, plus an absolute control. The treatments were distributed using a completely randomized design, with 6 treatments and 10 repetitions. The method of dual sowing in plates with potato culture medium, dextrose and agar was used for the confrontations. To the total colonization of the plates, assemblies were prepared to observe under an optical microscope whether mycoparasitism was present or not. Subsequently, the plates were covered with sterile sand and 8 seeds of var. cowpea, it was constantly irrigated with sterile water and the percentage of germination, the incidence and severity of fungal chupadera was evaluated after 25 days. The data were transformed into angular values and an analysis of variance and the Tukey test. Strains of Trichoderma virens exerted an antagonistic effect on Rhizoctonia solani, producing mycelial fragmentation and mycoparasitism. The treatment only with R. solani obtained 5% of germination, and 100% of incidence and severity of fungal chupadera; in the other treatments the germination was 100%, the incidence fluctuated between 1.25 and 8.75%. and the severity between 0.31 to 2.8%. These results indicate that T. virens can be a sustainable alternative for the control of R. solani